Thymic Tumours in Children - Aleksandra Napieralska; Leszek Miszczyk (MDPI AG, 2021)
Thymomas are very rare neoplasms in children and they represent less than 1% of mediastinal tumours in the paediatric population. The aim of our study was to assess the long-term treatment results of children with thymic tumours. A total number of eight children (four boys and four girls) with thymic tumours were identified. Median age at diagnosis was 7 years. In seven of them, thymoma was diagnosed; in one, a thymic carcinoma was diagnosed. In five of them, the WHO type was assessed: in two of them, the B1 type was found; in one, B2 was found; in one, AB was found, and in one, C was found. In all but one, surgery was the first-line treatment, but six patients had only partial resection. One patient started treatment with chemotherapy and four others received chemotherapy after the surgery. Radiotherapy was applied in six patients, with a median total dose of 37.5 Gy. Follow-up ranged from 8.5 to 273.5 months, with a median of 6.1 years. During this time, four patients died: one due to progression of the disease, and in the other three, the reason for death was unknown. In all evaluated patients, complete regression was observed (100% local control). Two-, 5- and 10-year OS and PFS were 85% and 72%, 51% and 54%, 51% and 54%, respectively. Combined treatment could provide satisfactory results in thymoma patients. There is a need for further, larger studies, which could help to establish optimal management strategies.